2005
DOI: 10.1124/jpet.105.084129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PAI-039 [{1-Benzyl-5-[4-(trifluoromethoxy)phenyl]-1H-indol-3-yl}(oxo)acetic Acid], a Novel Plasminogen Activator Inhibitor-1 Inhibitor, in a Canine Model of Coronary Artery Thrombosis

Abstract: We tested a novel, orally active inhibitor of plasminogen activator inhibitor-1 (PAI-1) in a canine model of electrolytic injury. Dogs received by oral gavage either vehicle (control) or the PAI-1 inhibitor PAI-039 [{1-benzyl-5-[4-(trifluoromethoxy)phenyl]-1H-indol-3-yl}(oxo)acetic acid] (1, 3, and 10 mg/kg) and were subjected to electrolytic injury of the coronary artery. PAI-039 caused prolongation in time to coronary occlusion (control, 31.7 Ϯ 6.3 min; 3 mg/kg PAI-039, 66.0 Ϯ 6.4 min; 10 mg/kg, 56.7 Ϯ 7.4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Recently, an orally active small molecule antagonist of PAI-1 (PAI-039) was shown to inhibit plasma PAI-1 activity and accelerate fibrinolysis of coronary artery thrombosis in dogs [Hennan et al, 2005] and provide protection against angiotensin II-induced aortic remodeling in mice [Weisberg et al, 2005]. These studies offer the much-awaited proof-of-concept for PAI-1 inhibitors in treating cardiovascular complications, thereby endorsing the concept of PAI-1 inhibitors to treat secondary complications of obesity.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, an orally active small molecule antagonist of PAI-1 (PAI-039) was shown to inhibit plasma PAI-1 activity and accelerate fibrinolysis of coronary artery thrombosis in dogs [Hennan et al, 2005] and provide protection against angiotensin II-induced aortic remodeling in mice [Weisberg et al, 2005]. These studies offer the much-awaited proof-of-concept for PAI-1 inhibitors in treating cardiovascular complications, thereby endorsing the concept of PAI-1 inhibitors to treat secondary complications of obesity.…”
Section: Discussionmentioning
confidence: 96%
“…Hemostasis and the effects of PAI-1 gene inactivation have also been studied in PAI-1-deficient mice, with neither spontaneous bleeding nor delayed rebleeding evident (34). In addition, PAI-1 inhibitors have been evaluated in preclinical models of coronary occlusion and shown to exert an antithrombotic effect without altering homeostasis (35). Furthermore, in vitro studies demonstrated that PAZ-417 does not inhibit tPA-initiated lysis of clots formed with either reptilase or thrombin, further showing that clot dissolution is unperturbed.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, PAI-1 synthesis is stimulated by a variety of other factors, including cytokines, lipids, and growth factors, and its production by and action on the vasculature can directly impact the etiology of atherosclerosis. 20 Because PAI-039 is an orally active direct inhibitor of PAI-1 that exhibits efficacy in models of acute thrombosis and accelerated atherosclerosis, 13,21,22 we decided to evaluate its effects on adipose tissue development and diet-induced obesity. PAI-039 dose-dependently reduced both basal and glucose-stimulated active PAI-1 antigen in human preadipocytes without affecting PAI-1 gene expression, indicating that the inhibition of PAI-1 was through direct interaction with the target protein.…”
Section: Discussionmentioning
confidence: 99%